SCIENTIFIC AND METHODOLOGICAL PRINCIPLES OF FORMING A RELIABLE EXPERT CONCLUSION (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the topical issue of forming a reliable opinion of an expert. The paper analyzes the theoretical principles and practical aspects of ensuring the objectivity and scientific validity of expert research. Various factors affecting the reliability of the expert's opinion are considered, such as: the expert's qualifications, research methods, the quality of the investigated objects, as well as the organizational and legal conditions for the examination. The article presents the factors that ensure the scientific validity and reliability of the expert opinion.
Keywords: expertise; expert opinion; reliability; scientific and methodological principles; objectivity; expert qualification; research methods; forensic examination; criminology